Simulação e projecto de processos químicos considerando aspectos económicos e ambientais - Teresa M. Mata (2006)
In this article the hydrodealkylation (HDA) process is studied and two process alternatives are compared: removing and recycling biphenyl. Since the unwanted biphenyl is formed by a reversible reaction the alternative of recycling biphenyl with toluene to let it build up to an equilibrium level in the reactor system is compared with an alternative where biphenyl is removed. The amounts of open and fugitive emissions are examined, assuming that 0.1% of each stream in a flowsheet is lost as a fugitive emission, and the respective potential environmental impacts are evaluated. In this way one could determine the fraction of the emissions (open or fugitive) that are more important or contribute more to the potential environmental impacts. The results show that higher economic potentials and lower potential environmental impact are obtained when biphenyl is removed from the process. In this case, the economic and environmental optimum occurs for a toluene conversion around 0,75. Despite the fact that recycling biphenyl allows one to eliminate the toluene tower and costs associated with biphenyl waste treatment, the reactor costs and process flowrates increase, increasing the capital and operating costs. This is a major result of this study since it shows the trade-offs between the two alternatives, allowing one to choose the most economical and environmentally beneficial process design option.